What is the pH, Fe and Cl2 content of cosmetics we use? – a pilot study on safety of skin care products - Nieradko-Iwanicka, Barbara; Chrobok, Katarzyna; Skolarczyk, Justyna; Pekar, Joanna (Polish Journal of Public Health, 2018)
Introduction. The skin is one of the largest organs of the body protecting from external insults in order to maintain homeostasis. It plays many roles: in thermal, electrolyte, hormonal, metabolic, and immune regulation. Proper pH of skin plays a role in creation of skin barrier and resistance to external agents. Cl2 and Fe may irritate skin. If noxious factors are strong, they damage the tissues under the skin. When the insult is severe enough to overwhelm the protective function of the skin, it may manifest itself with acute or chronic skin injury. Therefore, it is important to know if the used skin products are safe.Aim. The objective of the study was to determine pH, Cl2 and Fe content in selected cosmetics.Material and methods. A total of 62 skin product samples were collected and divided into 4 groups: I soaps and gels, II hair cosmetics, III creams and balms, IV facial cosmetics. The pH, Cl2 and Fe content in each sample was determined three times and means were calculated. Data were analyzed with one way ANOVA followed by Tukey test. P